A lost destiny or world of warcraft? Unlocking the hidden power of designs. (September 2020) - Burbidge, Rosie
Abstract : Copyright protection is often unavailable for many game elements due to the dynamic nature of games where single still frames are automatically generated and consequently proving originality and copying can be challenging. Registered designs help fill this gap and are a powerful, but underused, weapon. This article explain how designs can be used by gaming companies and the issues that need to be considered before starting a filing programme and the impact of Brexit on everything – to the extent that this can be known in mid-2020.